Analysis of the Effect of Flash Sales, Lifestyle, Rating Product, and Influencer Endorse on Consumer Purchase Decisions in the Tiktokshop Application - Pasaribu, Nurmayanti Septiarani; Simanjorang, Elida Florentina Sinaga; Siregar, Marlina (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The Tiktokshop platform is currently very popular among Indonesians as a reference for online shopping. This is because Tiktokshop has developed product marketing creativity in the form of videos, live streaming, and holding price discounts (flash sales) to enable sales on Tiktokshop to use endorsed influencer services in introducing and promoting their products. This study aims to analyze the influence of flash sales, lifestyle, and product ratings, and endorse influencers on consumer purchasing decisions in the Tiktokshop application. The method used for data collection in research is through questionnaires. The number of samples taken was 100 respondents. This study used a non-probability sampling method, namely purposive sampling. Test data analysis using the SPSS program. The results of this study indicate that flash-sale and endorsed influencers have no significant effect on consumer purchasing decisions in the Tiktokshop application, but lifestyle and product ratings have a significant effect on consumer purchasing decisions in the Tiktokshop application.